Relationship between Periodontal Status and Associated Factors in Pregnant Women in Kashan; a Cross-sectional Study - Ghorbani, Zahra; Ehteram, Mohammad; Namdari, Mahshid; Mostafapour, Parmida (Journal of Dental School, 2024)
Background: Hormonal changes during pregnancy may act as a modifying factor of the pathogenesis of periodontal disease, being reported as a potential risk factor of adverse pregnancy outcomes. This study was accomplished to investigate the level of periodontal disease in pregnant women and to identify associated risk factors in a population of pregnant women in Kashan in 2017. Material and methods: A total of 128 pregnant women in the second and third trimester of pregnancy were recruited. Demographic data, oral health behaviors and socioeconomic status were determined by using a standard questionnaire. The periodontal condition was evaluated by Community Periodontal Index (CPI), Clinical Attachment Loss (CAL) and Bleeding on Probing (BOP) indices. Results: The mean (standard deviation) age of the samples was 24.35 (3.4). More than half of the participants (53.1%) were in the second trimester of pregnancy. A quarter of pregnant women had visited a dentist within the past year, of which more than 74% visit the dentist for pain or treatment. About half of the participants (50.8%) brushed their teeth daily, but only 10% of mothers had daily flossing habit. Periodontal screening is typically done using the Community Periodontal Index (CPI). Calculus had the highest score (49.2%) prevailing among the subjects, while prevalence of periodontitis (pocket depth>=3) was 35.2%. Pocket depth >3mm was more frequent in women with academic education, good socioeconomic status, women without history of pain, women who brush their teeth twice a day or more and women who visit the dentist (P <0.05). Conclusion: The findings of the present study shows that all the studied factors are considered as risk factors for periodontal disease in pregnant women.